(untitled) (Al-Academy, 2024)
Political theater is an art form that carries with it an awareness message and a strong social impact. Theater in this context is not just an entertainment means، but rather an artistic platform based on thought and artistic expression to explore issues of the present and the future. Political theater offers a unique window into the interaction between art and political reality، as it allows the audience to understand complex issues more deeply and analyze them through an artistic vision. Political theater constitutes a live artistic space that reflects transformations and developments in societies، as it sheds light on political conflicts، social injustice، and humanitarian challenges. Theater here is a means of stimulating public debate and encouraging critical thinking. which contributes to building collective awareness about important issues. This research aims to explore the role of political theater as an effective means of shaping the public’s point of view regarding contemporary political issues. This is done through the actor who presents the characters on stage in an artistic way، as the actor’s role comes as a vital part of this artistic and social process. The actor is not only a carrier of texts and characters، but he is also an effective means of conveying messages and understanding the meanings of contemporary issues. The research dealt with the concept of political theater and its development throughout the ages، with a focus on how it influences the formation of public opinion and stimulates critical thinking. The research also addressed the importance of the artistic language used in Political theater، and how characters and events appear on stage as a means of presenting and understanding political transformations. The research included four chapters. The first chapter was the methodological framework of the research، including the research problem، the importance of the research، the objectives of the research، and the limits of the research. The second section dealt with the theoretical framework of the research and included two sections and then indicators of the theoretical framework. The third section included the research community and analysis of a sample of a political play. Finally، The fourth chapter contains the results، conclusions، and a list of sources and references